Plastic is in the details: the impact of plastic pollution through a mesocosm experiment - Goulais, Maeva; Darinot-Thomas, Sophie; Mitta, Guillaume; Galgani, François; Saulnier, Denis; Benestan, Laura (Frontiers in Marine Science, 2024)
Microbial diversity plays key role in marine ecosystems, and quantifying the impact of plastic pollution on these organisms is essential to better anticipate and manage threats to these fragile ecosystems. In nine simplified tropical ecosystems (i.e. mesocosms), we tested a concentration gradient of macroplastics reflecting the amount of plastic released by pearl farms. In each mesocosm, we collected bacterial samples from three different compartments: macroplastics, water and animals, Tridacna maxima. The objective was to test how plastic concentration influences the bacterial community, whether certain bacteria respond similarly across these compartments, and to define a threshold concentration of plastic that would impact marine bacteria. We observed that over 70 % of the variability in the bacterial community was explained by the type of sample (51.8 %) and time (19.4 %). On a finer scale, we found that the abundance of 33 bacterial genera was significantly correlated with plastic pollution, with the highest concentration (4.05 g/L) accounting for the vast majority of the signal. The occurrence of these bacterial genera increased with high plastic concentrations, suggesting imbalanced competitive relationships favoring less pollutant-sensitive genera. Some of these bacteria were shared across compartments and have known ecological functions, including plastic degradation and pathogenicity. Our results align with prior studies that warn plastics can alter microbial interactions and promote the emergence of pathogenic families.